2022
DOI: 10.7554/elife.73260
|View full text |Cite
|
Sign up to set email alerts
|

A DCL3 dicing code within Pol IV-RDR2 transcripts diversifies the siRNA pool guiding RNA-directed DNA methylation

Abstract: In plants, selfish genetic elements including retrotransposons and DNA viruses are transcriptionally silenced by RNA-directed DNA methylation. Guiding the process are short interfering RNAs (siRNAs) cut by DICER-LIKE 3 (DCL3) from double-stranded precursors of ~30 bp that are synthesized by NUCLEAR RNA POLYMERASE IV (Pol IV) and RNA-DEPENDENT RNA POLYMERASE 2 (RDR2). We show that Pol IV's choice of initiating nucleotide, RDR2's initiation 1-2 nt internal to Pol IV transcript ends and RDR2's terminal transferas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
(55 reference statements)
1
34
0
Order By: Relevance
“…Previous reports showed that DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable sequence (23)(24)(25). Thus, we cannot exclude the possibility that the siRNAs with the 5′ A and the thermodynamically unstable ends are enriched at the DCL3-mediated cleavage steps but not at the loading step.…”
Section: Ago4 and Ago6 Actively Select 24a Sirnas Via Distinct Mechan...mentioning
confidence: 77%
See 1 more Smart Citation
“…Previous reports showed that DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable sequence (23)(24)(25). Thus, we cannot exclude the possibility that the siRNAs with the 5′ A and the thermodynamically unstable ends are enriched at the DCL3-mediated cleavage steps but not at the loading step.…”
Section: Ago4 and Ago6 Actively Select 24a Sirnas Via Distinct Mechan...mentioning
confidence: 77%
“…Sequencing of total small RNAs in plant cells showed that about 60% of 24-nt siRNAs have a 5′ A (18). This enrichment of 24A siRNAs can be explained by the biased selection of transcription start site (TSS) by Pol IV and the substrate specificity of DCL3: Pol IV TSSs exhibit preference for A or G at the +1 position (21), and DCL3 prefers to cleave dsRNA precursors from the end with 5′ A and/or unstable terminus (22)(23)(24)(25). On the other hand, sequencing of small RNAs loaded into AGO4/6 showed a slightly higher percentage of 24A siRNAs than total small RNAs (18), suggesting that 24A siRNAs are further enriched in the loading step.…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes physically associate (Haag et al, 2012) and carry out coupled reactions that transcribe target locus DNA sequences into double-stranded RNAs of ~25-40bp (Fukudome et al ., 2021; Huang et al, 2021; Singh et al, 2019). DICER-LIKE 3 (DCL3) then cuts the dsRNAs into siRNAs, guided by sequence and structural features at the ends of precursor duplexes (Loffer et al, 2022). Resulting dicing products consist of a 24 nt siRNA strand paired with either a 23 nt strand (24/23 duplexes) or a 24 nt strand (24/24 duplexes) (Loffer et al ., 2022; Nagano et al, 2014), one strand of which ultimately becomes stably associated with ARGONAUTE 4 (AGO4).…”
Section: Introductionmentioning
confidence: 99%
“…DICER-LIKE 3 (DCL3) then cuts the dsRNAs into siRNAs, guided by sequence and structural features at the ends of precursor duplexes (Loffer et al, 2022). Resulting dicing products consist of a 24 nt siRNA strand paired with either a 23 nt strand (24/23 duplexes) or a 24 nt strand (24/24 duplexes) (Loffer et al ., 2022; Nagano et al, 2014), one strand of which ultimately becomes stably associated with ARGONAUTE 4 (AGO4). The siRNAs are then thought to guide AGO4 to RdDM target loci by basepairing to transcripts generated by NUCLEAR RNA POLYMERASE V (Pol V) (Liu et al, 2018; Wierzbicki et al, 2008; Wierzbicki et al, 2009), with protein-protein interactions between AGO4 and the Pol V largest subunit (NRPE1), and/or the Pol V-associated protein, SPT5L also implicated in target locus interactions (Bies-Etheve et al, 2009; El-Shami et al, 2007; Li et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation